Changes in calf productivity and resistance as a result of using the lactulose-based feed additive - Voevodina Yulia A.; Novikova Tatyana V.; Shevchuk Vladimir B.; Gnezdilova Anna I.; Fialkova Evgenia A.; Vinogradova Yulia V.; Kuzin Andrey A. (BIO Web of Conferences, 2020)
Objective: the aim of the research is to make a comprehensive assessment of the prebiotic feed additive effect on calves. The experiment was carried out in work conditions on 10 black-and-white Holstein-cross calves at the age of 2 to 32 days. To conduct the experiment, an experimental group and a test group have been formed. Each group has included five milk-fed calves at the age of 2 days and older. All the calves have been given colostrum in their first 2–4 hours after birth and then they have been fed three times a day, at regular intervals. The following methods are used: clinical, microbiological, immunological and statistical. The article describes the prebiotic lactulose-based additive effect on the intestinal microbiocenosis development in one-month old calves and presents an assessment of humoral and cellular components of natural resistance in calves. The research results show a positive effect of the lactulose-based additive on the symbiotic microflora of the gastrointestinal tract that improves the natural resistance of the body and the physiological status of animals, reduces the disease duration and contributes to an increase in weight gain. After feeding the calves with the lactulose-containing preparation during their first month of life, the weight gain of each calf in the experimental group has been 21.8 kg, or + 51 % of the initial weight and in the test group 19.0 kg, or + 41 % of the initial weight. Feeding the additive has an impact on the two components of natural resistance: serum bactericidal activity in the experimental group calves has been higher by 17.8 % and the phagocytosis activity has been higher by 30.5%, compared to the test group calves. Feeding calves with the lactulose-containing additive helps reduce the illness duration, stimulates the increase in live weight and affects the natural resistance level of newborn animals positively.